An analysis of corporate social responsibility and its usefulness in catalysing ecosystem sustainability - Topal, R. Seminur; Ongen, Atakan; Filho, Walter Leal (INDERSCIENCE ENTERPRISES LTD, 2009)
Although current definitions of sustainability do not specifically refer to the stability of systems, this has proven to be an elementary requirement for competent behaviour. This is based on the fact that future generations will be able to fulfil their needs if the ecological, economical, and social systems are adaptable and capable of surviving. In order to be viable in the long-term, products, functions and organisational structures need to be united with the biology of nature and human kind; they must be correspondingly developed. Ecological aspects have often dominated the discussion concerning sustainability. This paper examines the perspectives of 'ecosystem sustainability' and 'social responsibility' from the risk management system point of view. It outlines some of the elements to be considered in preserving and extending the protection of habitats and biological diversity and some of the means that may be used in order to promote the use of CSR to foster the cause of ecological sustainability.
Keywords: corporate social responsibility; CSR; ecosystem sustainability; ecological sustainability; risk management system in CSR; Environmental Sciences & Ecology